The debated construct of labour exploitation: a scoping review of wage abuse - Carlino, Martina (2022)
One of the most common questions when addressing human and labour rights violations concerns what kind of policy prescriptions, regulations and enforcements could have a positive impact on the reduction of the incidence of those abuses and, eventually, on the remediation of the damages caused to the victims. However, it might be argued there are several violations showing a strong persistence, for which the impact of legal deterrents is not as straightforward as expected and, moreover, seems to be insufficient to determine a structural change. Labour exploitation can assume different forms and one of them is wage abuse. Decent work and modern slavery stand on a continuum; it is not so difficult to think about severe forms of labour exploitation, as well as simply unfair labour standards. What is more puzzling is how those practices become embedded within certain systems, internalised and normalised by the actors of the labour market. With the ultimate goal of shedding light on the underlying dynamics of this complex phenomenon and contributing to the understanding of how to possibly upset it, a systematic scoping review of the existent literature on wage abuse, at the crossroad of different disciplines, has been conducted. This scoping review aimed at identifying how research has been conducted and the types of evidence, getting a clearer understanding of the key concepts and definitions, identifying potential knowledge gaps and their nature, in an attempt to answer the following research questions: what is known about social norms, attitudes, and beliefs linked to wage exploitation in developed countries? Under what conditions does wage exploitation become an established/consolidated practice? Who are the (ideal) adult victims and perpetrators of wage exploitation? Among the most relevant insights that can be gained from the results of this scoping review, the importance of a holistic approach to the study of practices of labour exploitation wins the first place on the podium. Labour exploitation should not be analysed as an issue of industrial production only, but as a social phenomenon in which values, norms, and ethics play a crucial role. Second, the critical void produced by the absence of employers’ accounts of noncompliance, mistreatment, and abuse and their personification with the mere logics of profit in a capitalist economy poses some questions about how to interpret behavioural models of exploitation. Little is known and much seems to be shrouded in inextricable dynamics between agents and structures. Can a combination of pragmatism and labour process theory help us? If the final goal is to create a better and more compassionate world, the endurance of labour exploitation in our society may be better addressed adopting a fluid, conversational, political, solidarity- and community-oriented approach.